Flap fixation reduces seroma in patients undergoing mastectomy: a significant implication for clinical practice. Issue 1 (December 2016) - van Bastelaar, James; Beckers, Arianne; Snoeijs, Maarten; Beets, Geerard; Vissers, Yvonne
Abstract Background Seroma formation is a common complication following mastectomy for invasive breast cancer. Mastectomy flap fixation is achieved by reducing dead space volume using interrupted subcutaneous sutures. Methods All patients undergoing mastectomy due to invasive breast cancer or ductal carcinoma in situ (DCIS) were eligible for inclusion. From May 2012 to March 2013, all patients undergoing mastectomy in two hospitals were treated using flap fixation. The skin flaps were sutured on to the pectoral muscle using polyfilament absorbable sutures. The data was retrospectively analysed and compared to a historical control group that was not treated using flap fixation (May 2011 to March 2012). Results One hundred and eighty patients were included: 92 in the flap fixation group (FF) and 88 in the historical control group (HC). A total of 33/92 (35.9 %) patients developed seroma in the group that underwent flap fixation; 52/88 (59.1 %) patients developed seroma in the HC group (p  = 0.002). Seroma aspiration was performed in 14/92 (15.2 %) patients in the FF group as opposed to 38/88 (43.2 %) patients in the HC group (p  < 0.001). Conclusions Flap fixation is an effective surgical technique in reducing dead space and therefore seroma formation and seroma aspirations in patients undergoing mastectomy for invasive breast cancer or DCIS.